Effects of obesity and gestational diabetes mellitus on placental phospholipids. Issue 2 (August 2015) - Uhl, Olaf; Demmelmair, Hans; Segura, María Teresa; Florido, Jesús; Rueda, Ricardo; Campoy, Cristina; Koletzko, Berthold
Highlights Gestational diabetes and obesity alter placental glycerophospholipids. Placental PC(16:0/20:4) was identified as a source of arachidonic acid for the foetus. Placental phosphatidylethanolamine with arachidonic acid is associated with growth.